2019
DOI: 10.1124/mol.119.116780
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Burst Firing of Neurons in Nucleus Reticularis of the Thalamus by GluN2C-Containing NMDA Receptors

Abstract: The GluN2C subunit of the NMDA receptor is enriched in the neurons in the nucleus reticularis of the thalamus (nRT), but its role in regulating their function is not well understood. We found that deletion of GluN2C subunit did not affect spike frequency in response to depolarizing current injection or hyperpolarizationinduced rebound burst firing of nRT neurons. D-Cycloserine or CIQ (GluN2C/GluN2D positive allosteric modulator) did not affect the depolarization-induced spike frequency in nRT neurons. A newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 99 publications
0
26
0
Order By: Relevance
“…6F – I ). In addition, we have previously shown that intracerebroventricular injection of AICP does not affect basal locomotor activity in normal mice ( Liu et al, 2019 ). Together, electrophysiology and behavioral results demonstrate that DCS and AICP improves motor function in a mouse model of PD by facilitating the function of GluN2C-containing NMDA receptors in the GPe.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…6F – I ). In addition, we have previously shown that intracerebroventricular injection of AICP does not affect basal locomotor activity in normal mice ( Liu et al, 2019 ). Together, electrophysiology and behavioral results demonstrate that DCS and AICP improves motor function in a mouse model of PD by facilitating the function of GluN2C-containing NMDA receptors in the GPe.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, facilitation of GluN2C-containing receptors increases the firing of GPe fast spiking neurons. We have recently shown that in the nRT neurons, GluN2C ablation similarly does not affect basal excitability and burst firing, but facilitation of GluN2C-containing receptors by AICP modulates these properties ( Liu et al, 2019 ). Thus, it appears that increasing ongoing activity of GluN2C-containing receptors can modulate neuronal function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a recent study indicated that the GluN2A positive allosteric modulator GNE-0723 reduces low-frequency oscillations and epileptiform activity in a DS mouse model, providing evidence that NMDA receptor modulation could be a viable therapeutic option (Hanson et al, 2020). The GluN2C and GluN2D subunits of NMDA receptors have more restricted expression patterns, including relatively high expression in the thalamus, and recently developed GluN2C/2D-selective modulators could offer a means to tune thalamic function with more limited adverse effects (Acker et al, 2011; Khatri et al, 2014; Liu et al, 2019; Mullasseril et al, 2010; Swanger et al, 2018; Yi et al, 2020). Thus, the data presented here lay the foundation to explore glutamatergic synapse modulation as a possible therapeutic strategy to correct thalamic dysfunction in DS.…”
Section: Discussionmentioning
confidence: 99%